Aleatory uncertainties with global resistance safety factors for non-linear analyses of slender reinforced concrete columns. (15th March 2022) - Castaldo, Paolo; Gino, Diego; Marano, Giuseppe Carlo; Mancini, Giuseppe
Highlights: Several experimental tests on RC columns with increasing slenderness are considered. Non-linear numerical analyses are performed to define the global resistance. Probabilistic description of both material and geometric uncertainties is presented. Influence of the aleatory uncertainties on the global response is evaluated. Global resistance safety factors as a function of the slenderness are proposed. Abstract: The present study aims to investigate and evaluate the influence of aleatory uncertainties (i.e., material and geometric uncertainties) when non-linear numerical analyses are developed to assess the global resistance of slender reinforced concrete columns. For instance, a set of 40 experimental tests on slender reinforced concrete columns with different slenderness values known from the literature is considered. The experimental tests have been reproduced by means of non-linear numerical simulations adopting specific modelling hypotheses able to minimize the model uncertainty. Successively, the calibrated non-linear numerical models of the 40 columns are used to perform a probabilistic analysis of the global structural resistance (i.e., ultimate axial load) including material uncertainties only and, then, both geometric and material uncertainties. The two groups of the probabilistic investigation are useful to characterize the influence of both material and geometric uncertainties on the global structural response of slender RC columns. Finally, global resistance safety factors are proposed as a function of the slenderness discussing also the procedure to incorporate the proposed results within the use of the global resistance safety formats.